Internalizing Islamic Ecotheology through School Culture to Foster Eco-Character: Internalisasi Ekoteologi Islam melalui Budaya Sekolah untuk Menumbuhkan Karakter Peduli Lingkungan - Sabtina, Desi; Mahariah, Mahariah (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to analyze the process of internalizing Islamic ecotheological values through the school culture of Azzakiyah Islamic School in fostering students’ environmental care character. Employing a qualitative research method with a phenomenological approach, this research explores the lived experiences of teachers and students in undergoing the internalization process. Data collection techniques included in-depth interviews, observation, and documentation. The findings reveal that school culture plays a significant role as a medium of internalization, reflected in various activities such as project-based learning, outing classes, the 5R program, zero waste initiatives, and mentoring sessions. The internalization process occurs through three stages: value transformation, value transaction, and value transinternalization. These stages enable students not only to understand but also to internalize and practice ecotheological values in their daily lives. This process contributes to behavioral changes among students, including conserving energy, properly disposing of waste, and engaging in other environmentally responsible actions that reflect the indicators of an environmentally caring character. Highlights: Three-Stage Internalization: Values are instilled through transformation, transaction, and transinternalization. Cultural Practices: Activities like 5R, zero waste, and mentoring embed environmental responsibility. Behavioral Outcomes: Students demonstrate eco-friendly habits like energy conservation and waste management. Keywords: Islamic Ecotheology, School Culture, Environmental Care, Value Internalization